Efficacy of Minocycline in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis of Rodent and Clinical Studies - Sheng, Zhaofu; Liu, Yang; Li, Hongmin; Zheng, Wei; Xia, Bin; Zhang, Xin; Yong, V. Wee; Xue, Mengzhou (Frontiers in Neurology, 2018)
OBJECTIVES This study sought to evaluate the efficacy of minocycline for the management of acute ischemic stroke. BACKGROUND While previous meta-analysis has investigated the efficacy of minocycline in the treatment of acute stroke, it was criticized for its methodology. We present a new systematic review which differs from previous meta-analysis by adding new outcomes, and include new studies. METHODS The authors performed a literature search using PubMed, EMBASE, Cochrane Central Register of Controlled Trials, the Stroke Center, NIH’s Clinical Trials, Current Controlled Trials, and the WHO International Clinical Trials Registry Platform Search Portal before June 2018. The data meeting the inclusion criteria were extracted according to Cochrane methodology. Before meta-analysis, the studies were evaluated for publication bias and heterogeneity. Pooled estimates and 95% confidence intervals (CIs) were calculated using the random and ﬁxed-effects models. Sensitivity and subgroup analyses were also performed. The meta-analyses were conducted using Rev Man 5.3 software and Stata software 12.0. RESULT For clinical studies, 4 trials with 201 patients in the minocycline group and 195 patients in the control group met the inclusion criteria; 3 were randomized trials. Results showed that the groups receiving minocycline were superior to the control group, with significant differences in the NIHSS scores (mean difference [MD], -2.75; 95% CI, -4.78, 0.27; p=0.03) and mRS scores (MD, -0.98; 95% CI, -1.27, -0.69; p<0.01), but not Barthel Index Score (MD, 9.04; 95% CI, -0.78, 18.07; p=0.07). For rodent experiments, 14 studies were included. Neurological severity scores (NSS) was significantly improved (MD, -1.38; 95% CI, -1.64, -1.31; p<0.01) and infarct volume was obviously reduced (Std mean difference [SMD], -2.38; 95% CI, -3.40, -1.36; p<0.01) in the minocycline group. For infarct size, there was evidence of publication bias. CONCLUSIONS On the basis of the results of this meta-analysis of clinical trials and rodent experiments, minocycline appears as an effective therapeutic option for acute stroke.